2021
DOI: 10.1002/cbin.11713
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor interferon regulatory factor‐1 is an endogenous mediator of myocardial ischemia reperfusion injury

Abstract: Myocardial ischemia reperfusion (MIR) injury negatively affects the prognosis of acute myocardial infarction (AMI), while effective suppression of MIR injury remains a largely unmet clinical need. Interferon regulatory factors (IRF) are key players in chronic cardiac disorders such as cardiac remodeling. However, their roles in acute MIR injury remain largely unknown. In the current study, microarray data indicated that IRF1 expression was consistently changed in the human ischemic heart and ischemic reperfuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recent studies have identified IRF1 as a transcription factor regulating the occurrence and development of cardiovascular diseases 11 . In addition, IRF1 is an important endogenous mediator of ischaemic cardiomyopathy, with evidence suggesting that IRF1 overexpression could promote myocardial ischaemia–reperfusion injury 12,13 . Furthermore, IRF1 has been found to inhibit proliferation and exert a pro‐apoptotic effect in hepatocellular carcinoma cells 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified IRF1 as a transcription factor regulating the occurrence and development of cardiovascular diseases 11 . In addition, IRF1 is an important endogenous mediator of ischaemic cardiomyopathy, with evidence suggesting that IRF1 overexpression could promote myocardial ischaemia–reperfusion injury 12,13 . Furthermore, IRF1 has been found to inhibit proliferation and exert a pro‐apoptotic effect in hepatocellular carcinoma cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“… 11 In addition, IRF1 is an important endogenous mediator of ischaemic cardiomyopathy, with evidence suggesting that IRF1 overexpression could promote myocardial ischaemia–reperfusion injury. 12 , 13 Furthermore, IRF1 has been found to inhibit proliferation and exert a pro‐apoptotic effect in hepatocellular carcinoma cells. 14 A previous study found that IRF1 overexpression decreased VEGFA protein levels and suppressed osteosarcoma progression.…”
Section: Introductionmentioning
confidence: 99%